Ligand binding free energy and kinetics calculation in 2020. (9th January 2020) - Limongelli, Vittorio
Abstract: Ligand/protein binding (LPB) is a major topic in medicine, chemistry and biology. Since the advent of computers, many scientists have put efforts in developing theoretical models that could decode the alphabet of the LPB interaction. The success of this task passes by the resolution of the molecular mechanism of LPB. In the past century, major attention was dedicated to the thermodynamics of LPB, while more recent studies have revealed that ligand (un)binding kinetics is at least as important as ligand binding thermodynamics in determining the drug in vivo efficacy. In the present review, we introduce the most widely used computational methods to study LPB thermodynamics and kinetics. It is important to say that no method outperforms another, they all have pros and cons and the choice of the user should take carefully into account the system under investigation, the available structural and experimental data, and the goal of the research. A perspective on future directions of method development and research on LPB concludes the discussion. This article is categorized under: Molecular and Statistical Mechanics > Free Energy Methods Structure and Mechanism > Computational Biochemistry and Biophysics Molecular and Statistical Mechanics > Molecular Dynamics and Monte‐Carlo Methods Abstract : Ligand (L) binding to a molecular target (P) can be represented as a thermodynamic and kinetic process in which the binding constant Kb measures the thermodynamic stability of the binding complex (free‐energy), while the binding and unbinding rate constants kon and koff, respectively, define the kinetics with the koff determining the residence time of the ligand in the target structure. In this review, computational methods developed to estimate both the thermodynamics and kinetics of ligand/protein binding are discussed.